ANALISIS MAQASHID SYARIAH PADA STRATEGI ISTRI DALAM MENGELOLA NAFKAH SUAMI TANPA PEKERJAAN TETAP - Fikri Haikal, Mochmad (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2025)
Traditionally, the primary financial obligation (nafaqah) rests with the husband. However, modern economic instability often positions the wife as central to ensuring family economic continuity, especially when the husband lacks stable employment. Goals: This study aims to analyze the strategies employed by wives in managing family sustenance when their husbands are unemployed, viewed through the lens of Maqashid Syariah (the objectives of Islamic Law). Methods This research utilizes a qualitative approach with a library research design, focusing on normative legal texts and relevant socio-economic literature. The primary framework of analysis is the Maqashid Syariah approach, specifically al-Dharuriyyat al-Khamsah (the five essential needs). Results The analysis reveals that the wife’s proactive strategies including income contribution, financial management, and maintaining household harmony substantially contribute to achieving Maqashid Syariah. Specifically, these actions safeguard Hifzh al-Nafs (preservation of life/welfare) and Hifzh al-Nasl (preservation of progeny/family integrity) by securing basic necessities. The wife's adaptive role is a manifestation of the Islamic principles of mutual help (ta'awun) and seeking common good (jalb al-maslahah), adjusting gender roles without negating fundamental law, all to realize a stable and sakinah family.